Hard-switching reliability studies of 1200 V vertical GaN PiN diodes. (28th September 2018) - Slobodyan, O.; Smith, T.; Flicker, J.; Sandoval, S.; Matthews, C.; van Heukelom, M.; Kaplar, R.; Atcitty, S.
Abstract: Abstract : We report on reliability testing of vertical GaN (v-GaN) devices under continuous switching conditions of 500, 750, and 1000 V. Using a modified double-pulse test circuit, we evaluate 1200 V-rated v-GaN PiN diodes fabricated by Avogy. Forward current–voltage characteristics do not change over the stress period. Under the reverse bias, the devices exhibit an initial rise in leakage current, followed by a slower rate of increase with further stress. The leakage recovers after a day's relaxation which suggests that trapping of carriers in deep states is responsible. Overall, we found the devices to be robust over the range of conditions tested.